Exposer l’Ethnoécologie au Musée de l’Homme - Serge Bahuchet; Valérie Kozlowski; Marie Merlin; Agnès Parent (Revue d'ethnoécologie)
The Musée de l’Homme, which was opened October 15th, 2015, by the President of the Republic François Hollande, was entirely reshaped, in order to present a thematic course with our relations towards “nature” as a thread. The Musée de l’Homme leads us to think about human nature, as well as about our place within the biosphere and the evolution of life. In this pluridisciplinary itinerary, ethnoecology is inserted in little touches into several showcases: representation of nature (1001 ways of thinking the world), domestication and diversification of plants (with example of chilies), bees symbolism, portraits and contemporary ways of life (lifestyles with different impacts) and agrobiodiversity (with the example of maize in Mexico).